Teaching Engagement and Preschool Practitioners’ Disciplining Practice in Post-Corporal Punishment Era: A Correlational Quantitative Evaluation - O. Okeke, Chinedu I.; S. Ugwuanyi, Christian; C. Okeke, Charity; C. Ugwu, Gloria; N. Ngwoke, Anthonia; O. Ifelunni, Clara; N. Aye, Eucharia; T. Nnamdi, Ekeanyanwu (International Journal of Psychosocial Rehabilitation, 2024)
Studies have been conducted on the disciplining practices adopted by preschool teachers at thepost-corporal punishment era. However, there is dearth of empirical evidence on the nature ofthe relationship between the preschool teachers’ disciplining practice and their teachingengagement. Thus, the researchers explored the relationship between preschool teachers’disciplining practice and their teaching engagement using school type as a possible moderator.A correlational survey research design was adopted for the research using a sample of 156preschool teachers. Teacher disciplining practice and teaching engagement questionnaires wereused for data gathering. These instruments were face validated and trial tested yielding internalconsistency reliability indices of 0.79 and 0.82 respectively using the Cronbach alphamethod.Linear regression analysis was conducted to answer the research questions and test thecorresponding null hypotheses at 5% probability levels.The results of the analysis showed thatpreschool teachers’ disciplining practice had as significant (p< .05) positive relationship withteaching engagement. It was also revealed that school type had significant (p< .05) moderating influence on the relationship between preschool teachers’ disciplining practice and teachingengagement.This implies that when preschool teachers adopt better classroom discipliningpractice, they will have good and effective teaching engagement.